Exogenous Expression of Human Protamine 1 (hPrm1) Remodels Fibroblast Nuclei into Spermatid-like Structures - Domenico Iuso; Marta Czernik; Paola Toschi; Antonella Fidanza; Federica Zacchini; Robert Feil; Sandrine Curtet; Thierry Buchou; Hitoshi Shiota; Saadi Khochbin; Grazyna Ewa Ptak; Pasqualino Loi (Cell Reports, 2015)
Protamines confer a compact structure to the genome of male gametes. Here, we find that somatic cells can be remodeled by transient expression of protamine 1 (Prm1). Ectopically expressed Prm1 forms scattered foci in the nuclei of fibroblasts, which coalescence into spermatid-like structures, concomitant with a loss of histones and a reprogramming barrier, H3 lysine 9 methylation. Protaminized nuclei injected into enucleated oocytes efficiently underwent protamine to maternal histone TH2B exchange and developed into normal blastocyst stage embryos in vitro. Altogether, our findings present a model to study male-specific chromatin remodeling, which can be exploited for the improvement of somatic cell nuclear transfer.